Challenges in managing large-scale agile software development transformation - Aaltonen, Jenni (My University, 2014)
Adapting and scaling up agile concepts, which are characterized by iterative, self-directed, customer value focused methods, may not be a simple endeavor. This thesis concentrates on studying challenges in a large-scale agile software development transformation in order to enhance understanding and bring insight into the underlying factors for such emerging challenges. This topic is approached through understanding the concepts of agility and different methods compared to traditional plan-driven processes, complex adaptive theory and the impact of organizational culture on agile transformational efforts. The empirical part was conducted by a qualitative case study approach. The internationally operating software development case organization had a year of experience of an agile transformation effort during it had also undergone organizational realignment efforts. The primary data collection was conducted through semi-structured interviews supported by participatory observation. As a result the identified challenges were categorized under four broad themes: organizational, management, team dynamics and process related. The identified challenges indicate that agility is a multifaceted concept. Agile practices may bring visibility in issues of which many are embedded in the organizational culture or in the management style. Viewing software development as a complex adaptive system could facilitate understanding of the underpinning philosophy and eventually solving the issues: interactions are more important than processes and solving a complex problem, such a novel software development, requires constant feedback and adaptation to changing requirements. Furthermore, an agile implementation seems to be unique in nature, and agents engaged in the interaction are the pivotal part of the success of achieving agility. In case agility is not a strategic choice for whole organization, it seems additional issues may arise due to different ways of working in different parts of an organization. Lastly, detailed suggestions to mitigate the challenges of the case organization are provided.